A new species of Phanerothecium (Monogenea, Oogyrodactylidae), in Hypostomus regani (Loricariidae) from southeast Brazil - Vianna, Rogério Tubino; Pelegrini, Larissa Sbeghen [UNESP]; Vieira, Diego Henrique Mirandola Dias [UNESP]; Azevedo, Rodney Kozlowiski de; Abdallah, Vanessa Doro (FapUNIFESP (SciELO), 2022)
A new species of Phanerothecium Kritsky & Thatcher, 1977 (Oogyrodactylidae Harris, 1983) is described from locariid fish from southeast Brazil. Phanerothecium macrosomum n. sp. (Oogyrodactylidae) is described from the body surface of Hypostomus regani (Ihering, 1905) (Loricariidae). It is characterized by an armed male copulatory organ containing spines of different size from proximal to distal extremity, short peduncle and robust haptor.
Uma nova espécie de Phanerothecium (Monogenea, Oogyrodactylidae), de Hypostomus regani (Loricariidae) do sudeste do Brasil
Keywords: Batalha River; Brazilian siluriforms; freshwater fish; Neotropical region; Oogyrodactylidae